PENGEMBANGAN APLIKASI PEMBELAJARAN TAJWID AL-QUR’AN BERBASIS AUGMENTED REALITY STUDY KASUS DI MADRASAH MIFTAHUL ULUM 22 KARANG NONGKO - Kurniawan Wahyu Haryanto; Muhammad Rohimin (STMIK YADIKA BANGIL, 2020)
Abstract : In the digital era as it is today, children's interests tend to be more easily saturated to learn to understand the reading and mahorijil letters of the Qur'an delivered by the clerics and clerics that is with methods that are less in demand by children such as the question and answer method, lecture method, discussion method, assignment method and iqra 'method in studying and understanding letters, mahroj and tajwid. The library research method is this research that contains how to learn tajwid knowledge by utilizing interactive teaching tools using Augmented Reality (AR) technology. The purpose of this study is how to study and apply the Qur'an and its recitation law using the Augmented Reality (AR) method and visualize images on Augmeted Reality markers in realtime to provide an explanation to users of this application.This application is used so that users can understand how to read the Qur'an properly and correctly, this Augmented Reality (AR) technology combines elements of audio, images, videos and quizzes aimed at increasing the interest of millennials who love reading the Qur'an while adding insight into multimedia technology. Keywords : Android, Augmented Reality, Mobile, Android Learning School Environment